Prevention of diseases after menopause. (October 2014) - Lobo, R. A.; Davis, S. R.; De Villiers, T. J.; Gompel, A.; Henderson, V. W.; Hodis, H. N.; Lumsden, M. A.; Mack, W. J.; Shapiro, S.; Baber, R. J.
Abstract Women may expect to spend more than a third of their lives after menopause. Beginning in the sixth decade, many chronic diseases will begin to emerge, which will affect both the quality and quantity of a woman's life. Thus, the onset of menopause heralds an opportunity for prevention strategies to improve the quality of life and enhance longevity. Obesity, metabolic syndrome and diabetes, cardiovascular disease, osteoporosis and osteoarthritis, cognitive decline, dementia and depression, and cancer are the major diseases of concern. Prevention strategies at menopause have to begin with screening and careful assessment for risk factors, which should also include molecular and genetic diagnostics, as these become available. Identification of certain risks will then allow directed therapy. Evidence-based prevention for the diseases noted above include lifestyle management, cessation of smoking, curtailing excessive alcohol consumption, a healthy diet and moderate exercise, as well as mentally stimulating activities. Although the most recent publications from the follow-up studies of the Women's Health Initiative do not recommend menopause hormonal therapy as a prevention strategy, these conclusions may not be fully valid for midlife women, on the basis of the existing data. For healthy women aged 50–59 years, estrogen therapy decreases coronary heart disease and all-cause mortality; this interpretation is entirely consistent with results from other randomized, controlled trials and observational studies. Thus. as part of a comprehensive strategy to prevent chronic disease after menopause, menopausal hormone therapy, particularly estrogen therapy may be considered as part of the armamentarium.